Truth, lies and advertising: the art of account planning - Steel, Jon (New york: John wiley, sons, inc., 1998)
No room for the mouse, silent portners, the blind leading the bland, peeling the onion, the ficherman`s guide, ten houservises in dos movies, serendepity.
Keywords: Publicidad - Medios y Agencias